Сезонна варіабельність кріорезистентності сперматозоїдів та репродуктивних характеристик цапів зааненської породи - Bogdaniuk , Anastasiia; Garkavii , Volodymyr; Petrushko , Maryna (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2022)
Cryopreservation of gametes is one of the important stages of assisted reproductive technologies (ART). To obtain high results using ART, it is essential to cryopreserve sperm in a favorable season, when gametes have a high ability to fertilize oocytes. The aim of this research was to study seasonal variability of spermatozoa cryoresistance and reproductive characteristics of Saanen goats. After removing the seminal fluid, the gametes of five mature animals were cryopreserved in a solution of 10% glycerol and 20% egg yolk. The ability of spermatozoa to fertilize was examined by the embryo development rate on day 7 of in vitro culture. Reproductive characteristics of Saanen goats during the breeding season were found to be featured by increased sperm concentration and motility. The survival rate of goat spermatozoa after cryopreservation is seasonally dependent, i. e. in the breeding season the number of viable spermatozoa was notably higher than in non-breeding one. The frequency of oocyte fertilization after the use of fresh and cryopreserved spermatozoa derived in different seasons was significantly higher in the breeding season group. The number of embryos which developed to the blastocyst stage was the lowest after fertilization of oocytes with cryopreserved spermatozoa obtained in the non-breeding season. It is concluded that sperm cryotolerance and reproductive characteristics of goats are higher in a breeding season compared to non-breeding one. The findings will allow to develop a strategy in the reproduction of farm animals for the food security of Ukraine. Probl Cryobiol Cryomed 2022; 32(1): 034–043